Energy substrates, metabolic regulators, and lipid accumulation during culture of in vitro-produced bovine embryos - Barceló-Fimbres, Moisés, author; Seidel, George E., Jr., advisor (Colorado State University. Libraries, 2007)
The main objective of this experiment was to optimize in vitro culture conditions for bovine embryonic development, using alternative energy sources and metabolic regulators. Replacing glucose with fructose in culture medium consistently increased blastocyst production per oocyte and decreased lipid content in bovine embryos. The use of phenazine ethosulphate (PES) or fetal calf serum (FCS) supplementation did not affect embryonic development; however, PES consistently decreased, and FCS increased lipid content of embryos compared to the control. There was no effect of glucose or fructose on survival of embryos after cryopreservation by slow freezing or vitrification; however, embryos-treated with PES to reduce lipid content resulted in improved cryotolerance, and FCS decreased cryotolerance compared to the control. Transfer of embryos treated with PES during in vitro culture did not affect pregnancy rates, conceptus losses, or fetal or post-natal development in calves born normally. The sex ratio of calves born was skewed toward males. This effect likely was due to a toxic effect of glucose to female embryos cultured in vitro. Therefore, the more expanded day 7 blastocysts were mostly male embryos.

A new, objective and less time consuming technique to quantify lipid accumulation using fluorescence of Nile red dye was validated. The progression of the early to expanded blastocyst resulted in decreased lipid content; also, the inner cell mass accumulated more lipids than the trophoblast compartment. Embryos were treated with various lipolytic agents. Forskolin reduced lipid content of embryos relative to controls, but caffeine and epinephrine did not affect lipid content of embryos at the doses tested. None of the lipolytic agents affected embryonic development except that high doses of caffeine were detrimental. A higher a percentage of oocytes derived from cow than post-pubertal heifer ovaries developed into blastocyst in vitro; however, more good quality oocytes were recovered per heifer ovary.
Keywords: bovine embryos; energy substrates; fructose; glucose; lipid; metabolic; anatomy and physiology; animals; environmental engineering